Evaluating the Impact of Semi-Immersive Virtual Reality on Urinary Catheterization Skills, Motivation, and Satisfaction in Nursing Students - Apriyanto, Bagus Sholeh; Akasyah, Wildan; Wahyuni, Sri; Rias, Yohanes Andy (STIKep PPNI Jawa Barat, 2024)
Aims: The basic core skill and competency nursing students need is urinary catheterization. Semi-immersive virtual reality (SIVR) based research innovations based on situational learning theory have not been widely used to improve student proficiency. This study aimed to analyze the skills, motivation, and satisfaction of nursing students with urinary catheterization learning before and after the implementation of SIVR. Methods: The study was designed as a pre-test and post-test randomized controlled trial (RCT). The study population was undergraduate nursing students at the Bhakti Wiyata Health Sciences Institute, Kediri. The SIVR group (n=52) received catheterization skill practice through SIVR, whereas the control group (n=52) was given 2-dimensional video learning. The results obtained were catheterization skills, motivation, and satisfaction, which were evaluated before and after the intervention. In this study's statistical test analysis, the chi-square test and the independent t-test were used. Results: Post-test results showed a significant improvement in catheterization skills in the SIVR group (M = 92.74, SD = 1.05, p = 0.032) compared to the control group (M = 79.95, SD = 1.51), a significant improvement in motivation in the SIVR group (M = 6.48, SD = 0.54, p = 0.010) compared to the control group (M = 5.23, SD = 0.49), and a significant improvement in satisfaction in the SIVR group (M = 3.49, SD = 0.83, p = 0.024) compared to the control group (M = 2.88, SD = 0.52). Conclusion: SIVR simulation and video learning can improve nursing students' skills, motivation, and satisfaction. SIVR program learning can be recommended as an intervention for the effectiveness of the quality of practical learning following current technological advances and in the long term it is expected to improve graduates' practical skills.